Mitigation of carbon steel biocorrosion using a green biocide enhanced by a nature-mimicking anti-biofilm peptide in a flow loop - Wang, Di; Unsal, Tuba; Kumseranee, Sith; Punpruk, Suchada; Saleh, Mazen A.; Alotaibi, Mohammed D.; Xu, Dake; Gu, Tingyue (Bioresources and bioprocessing, 2022)
Biocorrosion, also called microbiologically influenced corrosion (MIC), is a common operational threat to many industrial processes. It threatens carbon steel, stainless steel and many other metals. In the bioprocessing industry, reactor vessels in biomass processing and bioleaching are prone to MIC. MIC is caused by biofilms. The formation and morphology of biofilms can be impacted by fluid flow. Fluid velocity affects biocide distribution and MIC. Thus, assessing the efficacy of a biocide for the mitigation of MIC under flow condition is desired before a field trial. In this work, a benchtop closed flow loop bioreactor design was used to investigate the biocide mitigation of MIC of C1018 carbon steel at 25 °C for 7 days using enriched artificial seawater. An oilfield biofilm consortium was analyzed using metagenomics. The biofilm consortium was grown anaerobically in the flow loop which had a holding vessel for the culture medium and a chamber to hold C1018 carbon steel coupons. Peptide A (codename) was a chemically synthesized cyclic 14-mer (cys-ser-val-pro-tyr-asp-tyr-asn-trp-tyr-ser-asn-trp-cys) with its core 12-mer sequence originated from a biofilm dispersing protein secreted by a sea anemone which possesses a biofilm-free exterior. It was used as a biocide enhancer. The combination of 50 ppm (w/w) THPS (tetrakis hydroxymethyl phosphonium sulfate) biocide + 100 nM (180 ppb by mass) Peptide A resulted in extra 1-log reduction in the sulfate reducing bacteria (SRB) sessile cell count and the acid producing bacteria (APB) sessile cell count compared to 50 ppm THPS alone treatment. Furthermore, with the enhancement of 100 nM Peptide A, extra 44% reduction in weight loss and 36% abatement in corrosion pit depth were achieved compared to 50 ppm THPS alone treatment. Graphical Abstract